Implementasi Penggunaan Alat Peraga Lidi Perkalian dalam Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas II SDN 05 Nan Sabaris - Nurmalis Nurmalis (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2015)
The background of this class research are the studying result and student’s motivation of mathematic lesson of grade II students in SDN 05 Nan Sabaris, Nan Sabaris District, Padang Pariaman Regency is low because the studying activity there is not maximal. Studying mathematic in class is still boring. In other hand, there is no precise studying strategy in this case and the method that used is still conventional. Teacher is the only one who active in the studying activity, so teacher cannot see the student’s ability in reasoning. The students only listening to what the teacher is explaining about, without involving in that studying activity, so the students are hard to understand of what they have learned.Generally, the goal of this research is to recognize the increasing of student’s motivation and the studying result by using Lidi Perkalian application. This research is to answer the existing problems how Lidi Perkalian application can improve the motivation and the result of mathematic studying activity in grade II SDN 05 Nan Sabaris.The result of this research shows that the studying activity by using Lidi Perkalian application is giving positive impact to increase the motivation and studying result. It can be seen from the student’s understanding that going better in mathematic lesson, it that has been told by the teacher (the studying result is increased from first cycle to second cycle) both are 77.27% and 90.91%. On the second cycle, the students studying result is reached.